Enhancing Social Literacy Through Interactive Digital Media in Secondary School Social Studies - Lailaitul Qodriyah; Siti Fadiyah (Yayasan Cerdas Pedia Indonesia, 2025)
Indonesia currently faces a critical educational paradox characterized by high institutional access yet alarming deficits in functional literacy, particularly within Secondary Social Studies. This study investigates the utilization of interactive digital media to resolve this